2012
DOI: 10.1371/journal.pone.0045560
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the Injured Human Spinal Cord: Insights Revealed by Spinal Cord Functional MRI

Abstract: IntroductionWhile numerous studies have documented evidence for plasticity of the human brain there is little evidence that the human spinal cord can change after injury. Here, we employ a novel spinal fMRI design where we stimulate normal and abnormal sensory dermatomes in persons with traumatic spinal cord injury and perform a connectivity analysis to understand how spinal networks process information.MethodsSpinal fMRI data was collected at 3 Tesla at two institutions from 38 individuals using the standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…12,18 The development of methods to manage the hostile imaging environment and to account for cardiorespiratory-related motion has allowed improved applications to detect structural (such as diffusion and magnetization transfer imaging) and functional anomalies that occur in relation to traumatic injury of the spinal cord. 1,2,19,20 Other disorders, such as multiple sclerosis, have also benefited from spinal cord imaging. 21 Degenerative spinal disease, such as cervical spondylosis, is an increasing health burden due to the aging population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12,18 The development of methods to manage the hostile imaging environment and to account for cardiorespiratory-related motion has allowed improved applications to detect structural (such as diffusion and magnetization transfer imaging) and functional anomalies that occur in relation to traumatic injury of the spinal cord. 1,2,19,20 Other disorders, such as multiple sclerosis, have also benefited from spinal cord imaging. 21 Degenerative spinal disease, such as cervical spondylosis, is an increasing health burden due to the aging population.…”
Section: Resultsmentioning
confidence: 99%
“…For example, diffusion tensor imaging and magnetization transfer can be used to follow the integrity of white matter tracts in specific regions of the human spinal cord 1 ; fMRI can be used to track the spinal response to a particular stimulus, reflecting the integrity of specific functional circuits. 2 Recently, the microstructure of the corticospinal motor pathway was mapped; imaging characteristics of this map correlated with clinical function. 3 The ultimate goal of early detection of subclinical recovery or deterioration should be to personalize treatment strategies in both the acute and chronic phases of injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct spatial maps due to cardiac and respiratory noise sources have been revealed by single subject ICA (25)(26)(27), and a seed-based approach demonstrated correlations between ventral horns and between dorsal horns (28), but no group patterns of circumscribed motor or sensory networks have yet been found; also only a few investigations of task-based functional connectivity have been performed (29)(30)(31). One reason for the apparent lack…”
mentioning
confidence: 99%
“…In multiple sclerosis, magnetization transfer imaging [23], DTI fiber tractography [24], myelin water fraction estimation [25] and DTI metrics [26] have all been successfully correlated with clinical metrics. Spinal functional MRI has been applied both to multiple sclerosis [27] and chronic incomplete spinal cord injury [28]. The majority of quantitative spinal cord MRI studies are undertaken in ALS, MS and spinal cord injuries and very few dedicated imaging studies can be identified in hereditary spastic paraparesis and spinocerebellar ataxias [29].…”
Section: Future Directions and Novel Imaging Methodsmentioning
confidence: 99%